Odpowiedź :
1.
a)
[tex]x + 5 = 2(x + 1) \\ x + 5 = 2x + 2 \\ x- 2x = 2 - 5 \\ - x = - 3 \\ x = 3[/tex]
b)
[tex]6 - 4(y - 3) = 22 \\ 6 - 4y - 12 = 22 \\ - 4y = 22 + 12 - 6 \\ - 4y = 28 | \div ( - 4)\\ y = - 7[/tex]
c)
[tex]37 = 0.5(20 - 4x) - 7x \\ 37 = 10 - 2x - 7x \\ 37 - 10 = - 9x \\ - 9x = 27 | \div ( - 9) \\ x = - 3[/tex]
2.
a)
[tex] - 4x + 8 = 2(4 - 2x) \\ - 4x + 8 = 8 - 4x \\ - 4x + 4x = 8 - 8 \\ 0 = 0[/tex]
Ma nieskończenie wiele rozwiązań
b)
[tex]15y + 3(1 - 2y )= 9y \\ 15y + 3 - 6y = 9y \\ 15y - 6y - 9y = - 3 \\ 0 = - 3[/tex]
Brak rozwiązań
c)
[tex]2( x- 4) = 4(x - 2) \\ 2x - 8 = 4x - 8 \\ 2x - 4x = - 8 + 8 \\ - 2 x = 0 | \div ( - 2) \\ x = 0[/tex]
Brak rozwiązań
Myślę że pomogłem ;)